Problematic internet use in children between ages of 12-18 - Polat, Hakkı; Kök, Bayram; Tekeli, Muhammet Refik (Journal of Dependence, 2019)
Objective: The aim of this study is to investigate the factors affecting internet addiction in children aged 12-18 years.Method: The study sample consisted of a total of 1956 children aged at 12-18 years old. For this sampling, 3 middle school and 8 high school were selected randomly in Eskişehir. There have been obtained data for demographic properties and internet addiction status by the surveys which applied to children. Existing internet addiction status at the children and effective factors on this addiction were researched by the analyzing the collected data.Results: Approximately 15% of the children were addicted to internet use, and about 30% of the children were in the risk group. In addition, it was seen that the relationships and demographic characteristics of children with their social environment were effective on internet addiction.Conclusion: Children with internet addiction have problems in social isolation and control difficulties. However, it was determined that internet addiction is seen as the reason of academic failure and children with low social relations have higher risk of being addicted to internet.
Keywords: Dependency; social conditions; social behavior disorder